Struktur des Bankensystems und Geldpolitik - Hans E. Büschgen (Kredit und Kapital, 1971)
Structure of the Banking System and Monetary Policy Starting out from the investment preferences of banks and nonbanks, the increase in the formation of money substitutes by entities other than moneycreating banks is interpreted as a permanent improvement of the economy's liquidity concomitant with specialization in the banking field. In labour-dividing systems as in the U.S. A. and Great Britain, the moneycreating banks are uniformly subject to central bank control on account of the "control criterion"" - money creation. The decline in the significance of central bank money is accompanied by a decline in the significance of money supply policy. Institutions which make money substitutes available are not immediately affected by the central bank's control measures. A mixed-banking institution is subject to central bank control in respect of its money creation and of its (own) money substitutes which are held in lieu of cash and those which it offers to replace cash held by nonbanks. In a system of institutions with mutually complementary functions, only the commercial deposit banks are subject to the direct control of the central bank. The liquidity effects caused by formation of money substitutes by other financial institutions are not susceptible of direct control. The efficiency of the central bank's interest policy, which influences the liquidity effects, is greater in a mixed banking system than in a labourdividing system, if the flows of money market and capital market funds that are to be regulated converge in that system and disgruent financing predominates (criterion of maturity transformation). To the extent that the trend towards congruent financing runs parallel to the labour-dividing system, that is, the degree of maturity transformation diminishes, the effectiveness of the central bank's liquidity policy also decreases. Maturity transformation in the mixed-banking institution is, so to speak, a built-in stabilizer which supports the liquidity policy of the central bank.
Keywords: 330